Delineation of a new chromosome 20q11.2 duplication syndrome including the ASXL1 gene. Issue 7 (22nd May 2013) - Avila, Magali; Kirchhoff, Maria; Marle, Nathalie; Hove, Hanna D.; Chouchane, Mondher; Thauvin‐Robinet, Christel; Masurel, Alice; Mosca‐Boidron, Anne‐Laure; Callier, Patrick; Mugneret, Francine; Kjaergaard, Susanne; Faivre, Laurence
Abstract We report on three males with de novo overlapping 7.5, 9.8, and 10 Mb duplication of chromosome 20q11.2. Together with another patient previously published in the literature with overlapping 20q11 microduplication, we show that such patients display common clinical features including metopic ridging/trigonocephaly, developmental delay, epicanthal folds, and short hands. The duplication comprised the ASXL1 gene, in which de novo heterozygous nonsense or truncating mutations have recently been reported in patients with Borhing–Opitz syndrome. Because of craniofacial features in common with Borhing–Opitz syndrome, in particular metopic ridging/trigonocephaly, we suggest that duplication of ASXL1 contributes to the phenotype. These observations suggest a novel microduplication syndrome, and reporting of additional patients with molecular characterization will allow more detailed genotype–phenotype correlations. © 2013 Wiley Periodicals, Inc.